2017
DOI: 10.1556/2006.6.2017.017
|View full text |Cite
|
Sign up to set email alerts
|

Effects of time perspective and self-control on procrastination and Internet addiction

Abstract: Background and aimsCollege students experiencing stress show tendencies to procrastinate and can develop Internet addiction problems. This study investigated the structural relationship between time perspective and self-control on procrastination and Internet addiction. MethodsCollege students (N = 377) residing in South Korea completed the following questionnaires: the Pathological Internet Use Behavior Symptom Scale for Adults, the Zimbardo Time Perspective Inventory, the Self-Control Rating Scale, and the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
75
0
12

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(119 citation statements)
references
References 30 publications
12
75
0
12
Order By: Relevance
“…Taking individual school-related behaviors into account, procrastination stands out as a highly relevant risk factor for IUD symptoms in adolescence, confirming the results of other studies [49,50]. Procrastination is closely related to some clinical core symptoms of IUD.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Taking individual school-related behaviors into account, procrastination stands out as a highly relevant risk factor for IUD symptoms in adolescence, confirming the results of other studies [49,50]. Procrastination is closely related to some clinical core symptoms of IUD.…”
Section: Discussionsupporting
confidence: 86%
“…Those students also tend to procrastinate on their schoolwork, resulting in lower grades. Procrastination has been found to be significantly associated with IUD in adolescents [49,50] and adults [51,52]. In line with findings of comorbid ADHD in individuals with IUD [30,53], increased impulsivity equally seems to be an associated factor [21,54].…”
Section: Risk Factorsmentioning
confidence: 62%
“…A direct effect was found between FTP and SUD. Firstly, FTP had a negative predictive effect on SUD, and these results are consistent with those reported in previous studies [12,39]. Low levels of FTP indicate a significant association with fatalism and pessimism [70].…”
Section: Discussionsupporting
confidence: 91%
“…This inconsistency indicates that the generative mechanisms of behaviour and substance addiction may be distinct. One explanation is that individual FTP varies from person to person, influencing their feedback for risk perception, and FTP is considered a dynamic process [39,40]. Results indicate that cognitive-behavioural theory had successfully explained part of addiction behaviour, but more addict behavioural variances have yet to be explained fully.…”
mentioning
confidence: 95%
“…It means that student who has a problem with their selfcontrol tends to procrastinate on an academic task. Kim, Hong, Lee, and Hyun (2017)study also point out thatstudents who have high self-control reported have low on procrastination. Delaying or postpone behavior,indicate poor on self-control.…”
Section: Introductionmentioning
confidence: 86%